1990
DOI: 10.1111/j.1365-2303.1990.tb00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathology of malignant mesothelioma. Reappraisal of the diagnostic value of collagen cores

Abstract: The identification of malignant mesothelial cells in cytological smears prepared from serous effusions is still hampered by the lack of features specific for mesothelial differentiation. We examined the diagnostic value of collagen cores within clusters of tumour cells in cytological smears prepared from effusions from 43 patients with malignant mesothelioma and of 62 cases of metastatic adenocarcinoma. In Giemsa-stained smears collagen cores were detected in 51% of the cases of malignant mesothelioma and in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Fragments of tumor found in cytologic preparations of malignant pleural fluid are strongly associated with malignancy, and are much more frequently found in mesothelioma than in adenocarcinoma. These fragments often have an internal structure composed of collagen called a collagen core that, in one study, was found in 64% of mesothelioma cases versus 4% of adenocarcinoma cases (34). The source of these fragmentary tumor structures is unknown, but is speculated to be due to shedding of tumor cells or breakage of papillary structures.…”
Section: Discussionmentioning
confidence: 99%
“…Fragments of tumor found in cytologic preparations of malignant pleural fluid are strongly associated with malignancy, and are much more frequently found in mesothelioma than in adenocarcinoma. These fragments often have an internal structure composed of collagen called a collagen core that, in one study, was found in 64% of mesothelioma cases versus 4% of adenocarcinoma cases (34). The source of these fragmentary tumor structures is unknown, but is speculated to be due to shedding of tumor cells or breakage of papillary structures.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant mesothelioma, a tumor extremely resistant to chemotherapy, seems well suited for this approach: surgical resection generally provides a large amount of tumor that can be studied ex vivo, and mesothelioma is known to form spheroidal aggregates in vivo (27). Novel approaches in preclinical studies are also attractive for mesothelioma because it is a relatively uncommon tumor, thereby slowing accrual into clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether there is a degeneration or an anomalous production of this type of collagen which is also present in MS and EDS. In conclusion, we suspect that collagen [25, 26, 27, 28]may play a role in both these two syndromes and mesothelioma.…”
Section: Discussionmentioning
confidence: 99%